The Legal Framework Construction For Regulating Non-Judge Mediators Outside The Court - Azahra Hajar Gautama; Reka Dewantara; Hamidi Masykur (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2025)
This thesis discusses the basic legal construction of the regulation of non-judgmental mediators outside the court, with a focus on the incompleteness of the regulations in Articles 4, 11, and 36 of Supreme Court Regulation (Perma) No. 1 of 2016. These provisions do not adequately regulate the position, authority, and responsibilities of non-judgmental mediators, thus creating legal uncertainty and potentially weakening the legitimacy of non-litigation mediation results. This study aims to answer two research problems: (1) the urgency of establishing legal regulations regarding non-judgmental mediators outside the court; and (2) the appropriate basic legal construction for the regulation. The research method used is normative juridical with a statutory, conceptual, and comparative approach. The results of the study indicate that the urgency of establishing new regulations lies in the need to guarantee legal certainty, strengthen the position of mediators, and increase the effectiveness of mediation as an alternative dispute resolution. Based on Gustav Radbruch's theory of legal certainty, the current regulations do not fulfill the principle of legal certainty. Therefore, it is necessary to amend Articles 11 and 36 of Perma No. 1 of 2016, which covers the qualifications, legal status, accreditation, supervision, code of ethics, and accountability of non-judge mediators. This construction is based on Singapore's Mediation Act 2017 and analyzed using Maria Farida's legal theory. This proposal is expected to provide legal certainty and strengthen the non-litigation mediation system in Indonesia.